Spontaneous hemothorax: primary pleural epithelioid angiosarcoma - Amit Panjwani; Iqbal Singh; Nagendra Parvataneni; Phulkumari Talukdar (SpringerOpen, 2016)
Spontaneous hemothorax is a rare condition seen in coagulation and vascular disorders. Uncommonly, malignant neoplasms may cause spontaneous hemothorax. Primary pleural epithelioid angiosarcomas (excluding the cases with pleuropulmonary or chest wall involvement) are extremely rare pleural tumors, which may be mistaken for mesothelioma or adenocarcinoma, and only 19 cases (one of them from India) have been reported in the English literature, to date. It commonly occurs in older men, has a nonspecific clinicoradiological presentation, and carries a poor prognosis with no survivors beyond a year of establishing the diagnosis. We report a case of primary pleural epithelioid angiosarcoma presenting as a life-threatening spontaneous hemothorax. We also present a brief literature review on pleural angiosarcoma.